Perspectives on how to rebuild value chains with standards for food safety and against environmental degradation - Grace, Delia (CASA, 2020)
This platform will explore the underpinning issues that gave rise to the current pandemic and investigate the potential implications for investments and food safety, for example exploring the role of environmental sustainability standards for SMEs to reduce the risk of zoonotic disease transmission or pollution. Existing evidence suggests that the current pandemic is the result of lax standards in food safety and this is a trend across the globe. Scientists increasingly link food safety to the economic pressures driving biodiversity loss. If expanding supply chains and growing markets have enabled the conditions for this crisis, how do we avoid this happening again? Specifically how do we support the needs of investors with the emerging lessons? This panel will explore how investors can be responsible corporate citizens, responding to global consumer appetite without sacrificing public goods around health and environmental wellbeing, particularly in the context of emerging markets. Explicitly the discussion and resource dossier will address ideas to rebuild supply chains in ways that mitigate public health crises. This session is part of the “Rethinking Agri-Business Investments Through the Pandemic” e-conference series unpacking the response to COVID-19 for investors and SMEs in emerging markets, organised by the CASA programme.